A macroscopic approach for assessing the environmental performance of shared, automated, electric mobility in an intercity corridor - Fernandes, Pedro (2021)
This paper aims to evaluate the traffic and environmental performance when implementing scenarios with shared vehicles (SVs), electric vehicles (EVs) and automated vehicles (AVs) using a macro simulation modeling platform. Several scenarios were performed with different penetrations of shared, electric and automated vehicles to study the impact of CO2 and NOx emissions in terms of individual and system emissions in an intercity corridor in Portugal. A simplified model to estimate CO2 and NOx emissions for a representative vehicle based on average speed as input variable was used. The results suggest that for a group of realistic combinations of alternative mobility penetration scenarios, system CO2 emissions range from −22% to +6%, and system NOx emissions range from −35% to +5%. Emissions per vehicle show a range from −13% to +1% and from −18% to +8% for CO2 and NOx levels, respectively. Also, critical sectors were analyzed on both routes for the baseline scenario, which proved to be similar. Although increased shared mobility and electrification are generally positive, it is necessary to be aware that new mobility forms can lead to potentially adverse emission effects in some network sections. For instance, increased capacity on the highways caused by CAVs and consequent increase in average speed can be disadvantageous in the context of high penetration of electric vehicles that are more efficient at lower speeds.